Silica-bonded apatite scaffolds from calcite-filled preceramic polymers. Issue 13 (October 2016) - Fiocco, L.; Michielsen, B.; Bernardo, E.
Abstract: Silica-bonded apatite ceramics were successfully fabricated starting from preceramic polymers, in the form of silicone resins, incorporating powdered calcite (CaCO3 ). Silicone-calcite slurries were used for infiltrating sacrificial reticulated PLA scaffolds obtained by direct 3D printing. After cross-linking the mixture at room temperature, the samples were thermally treated at 350 °C to burn out the PLA, thus obtaining the desired scaffolds by negative replica. The samples were later ceramized at 600 °C, avoiding the decomposition of CaCO3 . A further treatment was applied to convert calcite into apatite (Ap), by immersion of samples in a phosphatizing bath (aqueous solution of sodium phosphate). It was demonstrated that the same procedure could be followed when replacing commercial CaCO3 with a material of biological origin, i.e. eggshell waste, resulting in a more extensive CaCO3 -to-Ap conversion. The formation of the desired crystalline phases was assessed by means of XRD analysis. The scaffolds were found to exhibit a porosity between 57 and 69%, considering both the voids in the reticulated structure and the micro-sized porosity of the struts, and an excellent compressive strength, in the order of 13–16 MPa.